Results on Bose–Einstein Correlations of Charged Hadrons in pp Collisions at 13 TeV in CMS - Padula, Sandra S. [UNESP] (Pleiades Publishing, 2022)
Abstract: Femtoscopic correlations between charged hadrons are measured over a broad multiplicity range, from a few particles up to about 250 reconstructed charged hadrons, in proton-proton collisions at (Formula presented.) s = 13 TeV. The results are based on data collected with the CMS detector at the LHC in 2015, during runs with a special low pileup configuration. Three analysis techniques with different dependencies on simulations are used to remove the non-Bose–Einstein background from the correlation functions, and are found to give consistent results. One-dimensional studies of the lengths-of-homogeneity, (Formula presented.), and the intercept parameter, (Formula presented.), have been carried out for both inclusive events and high multiplicity events selected using a dedicated online trigger. The measured lengths of homogeneity are studied as functions of particle multiplicity, pair average transverse momentum and pair average transverse mass. The results are compared with those from CMS collected at lower center-of-mass energies and to data from other LHC experiments, as well as with theoretical expectations from the color glass condensate and from hydrodynamic models.